2020
DOI: 10.1016/j.fuel.2019.116443
|View full text |Cite
|
Sign up to set email alerts
|

Low salinity effect on the recovery of oil trapped by nanopores: A molecular dynamics study

Abstract: Low salinity waterflooding (LSW) is an effective method for enhancing the oil recovery from many reservoirs, and its success has been traced to a host of low salinity effects. In this work, we perform molecular dynamics simulations to study the feasibility of recovering oil trapped by nanopores by lowering the reservoir salinity. The oil is initially trapped by a slit nanopore, with a portion of the oil protruding from the pore entrance. After the reservoir salinity is lowered, the thin brine films that separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Multicomponent Ion Exchange (MIE) mechanism demonstrates the effect of ion exchanges between surface-active components in the liquid and clay minerals [69][70][71]. The existence of divalent cations, such as Ca 2+ and Mg 2+ , bridges the negatively charged clay surface and carboxylate material, eliminates the organic material at the surface, and enhances water wetness in this process.…”
Section: Multicomponent Ion Exchangementioning
confidence: 99%
“…Multicomponent Ion Exchange (MIE) mechanism demonstrates the effect of ion exchanges between surface-active components in the liquid and clay minerals [69][70][71]. The existence of divalent cations, such as Ca 2+ and Mg 2+ , bridges the negatively charged clay surface and carboxylate material, eliminates the organic material at the surface, and enhances water wetness in this process.…”
Section: Multicomponent Ion Exchangementioning
confidence: 99%
“…As a result, the additional volume of oil may be produced depending on the salinity level and ionic composition of intrinsic and injecting brine in the porous medium, , initial rock wetting preference, chemical activity of the rock surface, ,, thermodynamic conditions of the core flooding experiment, ,,, and physicochemical properties of the oil–rock–brine (ORB) system, among others. The effectiveness of MSW flooding in reducing the adhesion force between oil and rock surface and possible improvement of oil recovery depends on the alteration of physicochemical equilibrium at the subpore scale. ,,, Figure illustrates different scales relevant to MSW flooding. At the pore scale, a trapped oil droplet adhered to the rock through a thin formation water film can be mobilized by the alteration of the equilibrium condition at the rock–water–oil interface.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…This can happen by the diffusion of ions inside the water film to/from the injected MSW that has reached the entrance of the pore neck (Figure c,d). Several studies have demonstrated that the diffusion of ions into the thin water film is slower than the pure Fickian diffusion process. ,, This is because the mobility of ions, i.e., charged species, in the thin water film is strongly affected by the electrically charged interfaces of oil–brine and rock–brine (Figure d) which creates an electric field. The mobility of ions with opposite charge compared to the charge at interfaces is considerably reduced due to the presence of repulsive electrostatic forces .…”
Section: Problem Descriptionmentioning
confidence: 99%
“…Zhao et al (2020) 2021) studied the intermolecular interactions between crude oil compositions including saturated hydrocarbons, aromatic hydrocarbons, resins, asphaltenes, and amphoteric surfactants 3-(decyl dimethylhydrazone) propane-1-sulfonates (DDPS). From the research mentioned above, it is exemplified that the molecular dynamics simulation technique has been an effective tool to study flow and displacement at the nanoscale (Fang 2019;Fang et al 2020). MD technology can manage to investigate the interaction between CO 2 and hydrocarbons in nanopores and analyze their properties change after contact.…”
Section: Introductionmentioning
confidence: 99%